2014
DOI: 10.1177/1536867x1401400307
|View full text |Cite
|
Sign up to set email alerts
|

A Stata Package for the Application of Semiparametric Estimators of Dose–Response Functions

Abstract: In many observational studies, the treatment may not be binary or categorical but rather continuous, so the focus is on estimating a continuous dose– response function. In this article, we propose a set of programs that semiparametrically estimate the dose–response function of a continuous treatment under the unconfoundedness assumption. We focus on kernel methods and penalized spline models and use generalized propensity-score methods under continuous treatment regimes for covariate adjustment. Our programs u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 24 publications
0
71
0
Order By: Relevance
“…The Hirano and Imbens method gives a parametric estimator that first estimates the GPS by regressing on the covariates and then estimates the eGFR based on the observed PFA concentration and fitted GPS [18]. The additive spline estimator estimates the ADRF in a two-step semiparametric process as outlined in Bia et al [19]. The first step is to parametrically model the GPS based on the covariates and create additive spline bases for the GPS and PFA.…”
Section: Methodsmentioning
confidence: 99%
“…The Hirano and Imbens method gives a parametric estimator that first estimates the GPS by regressing on the covariates and then estimates the eGFR based on the observed PFA concentration and fitted GPS [18]. The additive spline estimator estimates the ADRF in a two-step semiparametric process as outlined in Bia et al [19]. The first step is to parametrically model the GPS based on the covariates and create additive spline bases for the GPS and PFA.…”
Section: Methodsmentioning
confidence: 99%
“…Fong et al subsequently extended the CBPS methodology to quantitative exposures . Both Flores et al and Bia et al suggested using that generalized linear models could be used to estimate the propensity score function …”
Section: Using the Gps With Binary Outcomesmentioning
confidence: 99%
“…Alternative methods to estimating the dose‐response function have been described recently. Both Flores et al and Bia et al suggest that kernel methods and penalized spline methods can be used to estimate the dose‐response function …”
Section: Using the Gps With Binary Outcomesmentioning
confidence: 99%
See 2 more Smart Citations